Mid- to Long-Term Outcomes After Resection of Thoracic Dumbbell Tumors Managed by Laminectomy and Unilateral Total Facetectomy Without Instrumented Fusion. Issue 3 (April 2023) - Ishikawa, Yuya; Ohashi, Masayuki; Hirano, Toru; Matsuda, Michiharu; Akabane, Takeru; Kanno, Haruo; Hashimoto, Ko; Handa, Kyoichi; Aizawa, Toshimi; Suzuki, Tomoto; Shimamura, Yukihide; Watanabe, Kei
Study Design: Retrospective multicenter study. Objective: To evaluate mid- to long-term surgical outcomes of thoracic dumbbell tumors managed by laminectomy and unilateral total facetectomy without instrumented fusion. Methods: A total of 15 patients with thoracic dumbbell tumors who underwent primary resection by laminectomy and unilateral total facetectomy without spinal instrumented fusion between 2000 and 2015 were reviewed. Patient characteristics, surgical outcomes (including spinal alignment and stability), disc degeneration, pain, disability, and health-related quality of life were evaluated. Additionally, to analyze the impact of the affected levels on these outcomes, we divided the patients into 2 groups: a middle thoracic group and a thoracolumbar group. Results: The mean duration of follow-up was 100.5 months (range, 36-190 months). The affected level was T3-T4 or below in all patients. Although the local kyphosis angle (8.1° to 12.7°), thoracic kyphosis angle (25.6° to 33.9°), and coronal Cobb angle (6.6° to 9.5°) significantly increased from preoperative to the final visit ( P ≤ .02), no patient demonstrated spinal instability. From magnetic resonance imaging, no patient had a worse grade of disc degeneration in the affected level than those in the adjacent levels. The percentage of patients who presented with an Oswestry disability index ≤ 22% was 80%. Moreover, the surgical region did not adversely affect the outcomes. No patient required additional surgery due to spinal instability or deformity. Conclusions: Unilateral total facetectomy without fusion to resect thoracic dumbbell tumors caused neither spinal deformity nor instability requiring additional surgery at the mid- to long-term follow-up.